The evolution of the UV luminosity function of globular clusters in the E-MOSAICS simulations - Pfeffer, Joel; Kruijssen, Diederik; Reina-Campos, Marta (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present the evolution of the rest-frame ultraviolet (UV) properties of the globular cluster (GC) populations and their host galaxies formed in the